2023
DOI: 10.1111/1758-2229.13160
|View full text |Cite
|
Sign up to set email alerts
|

A new metabolic trait in an acetogen: Mixed acid fermentation of fructose in a methylene‐tetrahydrofolate reductase mutant of Acetobacterium woodii

Abstract: To inactivate the Wood–Ljungdahl pathway in the acetogenic model bacterium Acetobacterium woodii, the genes metVF encoding two of the subunits of the methylene‐tetrahydrofolate reductase were deleted. As expected, the mutant did not grow on C1 compounds and also not on lactate, ethanol or butanediol. In contrast to a mutant in which the first enzyme of the pathway (hydrogen‐dependent CO2 reductase) had been genetically deleted, cells were able to grow on fructose, albeit with lower rates and yields than the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…In a previous study we have found conversion of fructose to molecular hydrogen, formate, ethanol and lactate as end products in a Δ metVF mutant of A. woodii (Moon et al 2023a ). Here, we aimed to redirect fructose metabolism to lactate.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…In a previous study we have found conversion of fructose to molecular hydrogen, formate, ethanol and lactate as end products in a Δ metVF mutant of A. woodii (Moon et al 2023a ). Here, we aimed to redirect fructose metabolism to lactate.…”
Section: Resultsmentioning
confidence: 89%
“…This enzyme complex is known to be responsible for lactate oxidation during growth of A. woodii on lactate (Weghoff et al 2015 ). Recently, it has been reported that the lctBCD genes were highly expressed in the Δ metVF mutant grown on fructose where lactate was formed as a side product (Moon et al 2023a ). Therefore, to verify that a possible lactate formation was indeed catalyzed by LctBCD we genetically deleted the LDH/ETF complex.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations